Dung beetle and terrestrial mammal diversity in forests, indigenous agroforestry systems and plantain monocultures in Talamanca, Costa Rica - Harvey, Celia A. (2006)
In order to explore the importance of indigenous agroforestry systems for biodiversity conservation, we compared the abundance, species richness and diversity of dung beetles and terrestrial mammals across a gradient of different land use types from agricultural monocultures (plantains) to agroforestry systems (cocoa and banana) and forests in the BriBri and Cabe´car indigenous reserves in Talamanca, Costa Rica. A total of 132,460 dung beetles of 52 species and 913 tracks of 27 terrestrial mammal species were registered. Dung beetle species richness and diversity were greatest in the forests, intermediate in the agroforestry systems and lowest in the plantain monocultures, while dung beetle abundance was greatest in the plantain monocultures. The number of mammal tracks per plot was significantly higher in forests than in plantain monocultures, whereas mammal species richness was higher in forests than in either cocoa agro forestry systems or plantain monocultures. Species composition of both terrestrial mammals and dung beetles also varied across the different land use types. Our study indicates that indigenous cocoa and banana agroforestry systems maintain an intermediate level of biodiversity (which is less than that of the original forest but significantly greater than that of plantain monocultures) and provide suitable habitat for a number of forest-dependent species. Although the agroforestry systems appear to serve as favorable habitats for many terrestrial mammal species, their potential positive contribution to mammal conservation is being offset by heavy hunting pressure in the reserves. As in other agricultural landscapes, the conservation of biodiversity in Talamanca will depend not only on maintaining the existing forest patches and reducing the conversion of tradi tional agroforestry systems to monocultures, but also on reducing hunting pressure